고려인삼 중장기 수출확대를 위한 전략방안 연구 - 성명환 (한국농촌경제연구원, 2004)
A purpose of this study is to review a situation of world ginseng market and to build mid and long-ter strategies for expanding Korea ginseng export. World ginseng production is estimated to 70,000 tons worldwide in 2001. China produces 52,168 tons, 75% of total production and Korea produces 13,215 tons, 19% of total production. The USA and Canada produces 2,052 tons and 2,483 tons, respectively. Korea ginseng has very low price competitiveness. Korea ginseng had been sold ten times higher in price than chinese ginseng and 3 to 8 times higher than American ginseng in Hongkong ginseng market, 2001. Korea ginseng export has been rapidly decreased for this reason. Average production cost for 4-yeared Korea ginseng was Korean thousand won 10,375/10a which was 4.7 times higher than Korean thousand won 2,213/10a of Chinese ginseng. Farmer price and wholesale price of Korea undried ginseng were also 2.85 times and 4.72 times higher than those of chinese ginseng, 2002. If a local market is expanded and tariff is lowered, there would be a potentiality to increase ginseng import. Korea ginseng is famous for its high quality in oversea market but it tends to lose its marketshare due to weak price competitiveness. When we analyze Korea ginseng's competitiveness based on trade specialization index and revealed comparative advantage index, Korea's ginseng industry has comparative advantage and has specialized on trade. It is also revealed that net export of Korea ginseng is relative large and it takes large stakes in the market, but it needs to make a counter plan to constantly maintain longrun export comparativeness against imported ginseng. Export strategy - for example, product differentiation - is also needed to have a competitiveness against Hongkong, China and Canada. We propose differentiation strategies for Korea ginseng including export plan for each markets, diversifying export through analysis of importing conditions for major ginseng importing country Researcher: Myung-Hwan Sung, Dong-Phil Lee, Song-Soo Lim, Won-Jin Lee e-mail Address: mhsung@krei.re.kr
Keywords: 고려인삼; 인삼; 인삼산업